(3cJGH aj GNJdGa GdefGXQ hGdTYGYGJs - (3GbdjOSs
(3ChdgG (B:s
(3GdTYGY jNQL ef GdYjf Ydi NWhW eSJbjeI heYg jMOK hGdTcd GdPi jMjW Hg GdTYGY eNQhW QCSg Ydi GdYjf s
(3BNQgG (B:s
(3hcPdc GdCVdGY GdHGbjI JQi eJSGhjI GdCVdGY GdHGbjI hPdc eG CQOfG Cf fHjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1463s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs